Corak Bermazhab Jemaah Masjid Nurul Yaqin Kelurahan Manurunge Kecamatan Tanete Riattang Kabupaten Bone - Akbar, Ali; Arsyad, Azman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
Schools have a wide variety of shades. Therefore, this article raises the subject of the pattern of the Nurul Yaqin mosque congregation, Manurunge Village, Tanete Riattang District, Bone Regency. This study aims to determine the pattern of the Nurul Yaqin mosque congregation, Manurunge sub-district, Tanete Riattang District, Bone Regency. The type of research used for this research is in the form of field research or field studies. This research uses qualitative descriptive research method with a case study approach, using two data sources, namely primary data and secondary data where primary data is taken from answers from resource persons to questions asked by researchers. The results of this study show the style of the Nurul Yaqin Mosque congregation through their various ways of studying madhab such as participating in fiqh studies in the mosque or on social media, as well as how to practice the madhhab that each of them follows. Apart from these two things, the attitude of the Nurul Yaqin Mosque congregation in the differences between the Nurul Yaqin Mosque congregation in Bone Regency has different madhab patterns according to the school followed, some are Hanbali and some are Shafi'i, but the two followers of the two schools respect and tolerate each other.